The 4Cs in harm reduction programmes: a case of needle syringe exchange programme using total quality management / Sharifah Fadzlon Abdul Hamid …[et al.] - Abdul Hamid, Sharifah Fadzlon; Omar, Normah; Sulaiman, Suzana; Wee, Shu Hui; Mohd Zan, Norhazeera; Ab Fatah, Nur Shahida; Ismail, Rusli (Universiti Teknologi MARA Cawangan Selangor, 2013)
This paper intends to study the costs associated with harm reduction. Harm reduction is a way of dealing with behavior that damages the health of the persons involved and their community. Many individuals acquire these damaging behaviours (for example, smoking, drinking too much alcohol, practicing un-safe sex and drug abuse) are well aware of the adverse consequential effects on their health. Needle Syringe Exchange Programme (NSEP) is one such harm reduction programme recommended by the WHO (World Health Organization) to the Ministry of Health in Malaysia in 2005 and has produced encouraging results. Using the concept of Total Quality Management (TQM), the researchers identified and classified the costs involved in the harm reduction programme. The main principle of TQM with its emphasis on the cost of prevention is highly relevant in harm reduction programmes, which is similar to its emphasis on ‘prevention is better than cure’. Hence, this management accounting model which the researchers termed the 4Cs (currently in the process of being trademarked) is highly relevant and applicable in any harm reduction programme.